Folic Acid Mitigates Angiotensin-II-Induced Blood Pressure and Renal Remodeling - Pushpakumar, Sathnur B.; Kundu, Sourav; Metreveli, Naira; Sen, Utpal (PloS one, 2013)
Clinical data suggests an association between systolic hypertension, renal function and hyperhomocysteinemia (HHcy). HHcy is a state of elevated plasma homocysteine (Hcy) levels and is known to cause vascular complications. In this study, we tested the hypothesis whether Ang II-induced hypertension increases plasma Hcy levels and contributes to renovascular remodeling. We also tested whether folic acid (FA) treatment reduces plasma Hcy levels by enhancing Hcy remethylation and thus mitigating renal remodeling. Hypertension was induced in WT mice by infusing Ang II using Alzet mini osmotic pumps. Blood pressure, Hcy level, renal vascular density, oxidative stress, inflammation and fibrosis markers, and angiogenic- and anti-angiogenic factors were measured. Ang II hypertension increased plasma Hcy levels and reduced renal cortical blood flow and microvascular density. Elevated Hcy in Ang II hypertension was associated with decreased 4, 5-Diaminofluorescein (DAF-2DA) staining suggesting impaired endothelial function. Increased expression of Nox-2, -4 and dihydroethidium stain revealed oxidative stress. Excess collagen IV deposition in the peri-glomerular area and increased MMP-2, and -9 expression and activity indicated renal remodeling. The mRNA and protein expression of asymmetric dimethylarginine (ADMA) was increased and eNOS protein was decreased suggesting the involvement of this pathway in Hcy mediated hypertension. Decreased expressions of VEGF and increased anti-angiogenic factors, angiostatin and endostatin indicated impaired vasculogenesis. FA treatment partially reduced hypertension by mitigating HHcy in Ang II-treated animals and alleviated pro-inflammatory, pro-fibrotic and anti-angiogenic factors. These results suggest that renovascular remodeling in Ang II-induced hypertension is, in part, due to HHcy.